2023
DOI: 10.3390/ijms24054821
|View full text |Cite
|
Sign up to set email alerts
|

Spexin2 Is a Novel Food Regulator in Gallus gallus

Abstract: Spexin2 (SPX2), a paralog of SPX1, is a newly identified gene in non-mammalian vertebrates. Limited studies in fish have evidenced its important role in food intake and energy balance modulation. However, little is known about its biological functions in birds. Using the chicken (c-) as a model, we cloned the full-length cDNA of SPX2 by using RACE-PCR. It is 1189 base pair (bp) in length and predicted to generate a protein of 75 amino acids that contains a 14 amino acids mature peptide. Tissue distribution ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The mature peptide of SPX2 also contains 14 amino acids; however, its sequence differs from that of SPX1 at four positions[ 33 ]. Luciferase reporter assays have demonstrated that SPXs activate GAL receptors, GALR 2 and GALR3, but not GALR1 in humans, zebrafish[ 33 ], and chickens[ 35 , 36 ]. Interestingly, the potency of SPXs against GALR2 and GALR3 is similar to or greater than those of GAL in humans and zebrafish[ 33 ].…”
Section: Spexinmentioning
confidence: 99%
See 4 more Smart Citations
“…The mature peptide of SPX2 also contains 14 amino acids; however, its sequence differs from that of SPX1 at four positions[ 33 ]. Luciferase reporter assays have demonstrated that SPXs activate GAL receptors, GALR 2 and GALR3, but not GALR1 in humans, zebrafish[ 33 ], and chickens[ 35 , 36 ]. Interestingly, the potency of SPXs against GALR2 and GALR3 is similar to or greater than those of GAL in humans and zebrafish[ 33 ].…”
Section: Spexinmentioning
confidence: 99%
“…SPX mRNA is widely distributed in the central nervous system and peripheral tissues of chickens[ 34 , 35 , 36 ]. Fasting significantly increases the plasma SPX concentration[ 34 ] and hypothalamic mRNA levels of SPXs in chickens[ 35 , 36 ].…”
Section: Spexinmentioning
confidence: 99%
See 3 more Smart Citations